PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) DALAM POKOK BAHASAN TEOREMA PYTHAGORAS - Andi Rio Ramadhan (Jurnal Edukasi dan Penelitian Matematika, 2020)
Student Worksheet is one of the teaching materials that can support learning in achieving learning objectives. However, not all Student Worksheet are able to support learning optimally. In the Student Worksheet that was observed related to the Pythagorean theorem, there were still things that needed to be improved. This study aims to develop Student Worksheet on the subject of the Pythagorean theorem which is valid and practical using Contextual Teaching and Learning (CTL). This development research uses the Mckenney development model which consists of three stages, namely the preliminary stage, the prototyping stage, and the assessment stage. However, due to limited conditions, this study only reached the prototyping stage, especially prototype 2. Based on the results of the validation and practicalization questionnaires, it can be concluded that the Student Worksheet developed is valid and practical with characteristics relevant to the applicable curriculum, communicative, solid in material, appearance attractive, easy to use with a relatively short time, and the propagation process does not cost much. Keywords — Student Worksheets, contextual teaching and learning (CTL) approach, Pythagorean theorem